Neopterin is associated with plaque inflammation and destabilisation in human coronary atherosclerotic lesions. Issue 12 (17th June 2007) - Adachi, T; Naruko, T; Itoh, A; Komatsu, R; Abe, Y; Shirai, N; Yamashita, H; Ehara, S; Nakagawa, M; Kitabayashi, C; Ikura, Y; Ohsawa, M; et al.
Abstract : Background: Previous studies have shown that recent activation of the inflammatory response in coronary atherosclerotic lesions contributes to rapid progressive plaque destabilisation. Neopterin, a by-product of the guanosine triphosphate pathway, is produced by activated macrophages and serves as an activation marker for monocytes/macrophages. Objective: To elucidate the role of neopterin in coronary plaque destabilisation by immunohistochemical study of the presence of neopterin in coronary atherectomy specimens obtained from patients with stable angina pectoris (SAP) and unstable angina pectoris (UAP). Patients and methods: All patients underwent atherectomy of the primary atherosclerotic lesions responsible for SAP (n = 25) and UAP (n = 25). Frozen samples were studied with antibodies against smooth muscle cells, macrophages, T cells, neutrophils and neopterin. Results: In 22/25 patients with UAP, abundant neopterin-positive macrophages were found at the sites of coronary culprit lesions. However, in 25 lesions from patients with SAP, only 11 lesions showed neopterin positivity. Quantitatively, the neopterin-positive macrophage score was significantly higher (p<0.001) in patients with UAP than in patients with SAP. Moreover, the neopterin-positive macrophage score showed a significant positive correlation with the number of neutrophils or T cells, respectively (neutrophils, r  = 0.55, p<0.001; T cells, r  = 0.70, p<0.001). Conclusions: Neopterin can be considered as one of the significant factors in the process of plaque inflammation and destabilisation in human coronary atherosclerotic lesions. Its exact role in the process needs to be investigated further.